2017
DOI: 10.1093/humrep/dex073
|View full text |Cite
|
Sign up to set email alerts
|

Grandmaternal smoke exposure reduces female fertility in a murine model, with great-grandmaternal smoke exposure unlikely to have an effect

Abstract: This study was funded by the Australian Research Council, National Health and Medical Research Council, Hunter Medical Research Institute, Newcastle Permanent Building Society Charitable Trust, and the University of Newcastle Priory Research Centers in Chemical Biology, Healthy Lungs and Grow Up Well. The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In animal models, experimental studies showed that exposure to maternal smoking, similar to study findings regarding maternal nutritional status, was related to negative reproductive health outcomes in the adult offspring, including indicators of sub-fertility, lower ovarian reserve, and increased oxidative stress [68][69][70]. Consistent with these findings, in a prior study of women, maternal smoking during pregnancy was associated with earlier menopausal timing in the offspring [41].…”
Section: Discussionsupporting
confidence: 54%
“…In animal models, experimental studies showed that exposure to maternal smoking, similar to study findings regarding maternal nutritional status, was related to negative reproductive health outcomes in the adult offspring, including indicators of sub-fertility, lower ovarian reserve, and increased oxidative stress [68][69][70]. Consistent with these findings, in a prior study of women, maternal smoking during pregnancy was associated with earlier menopausal timing in the offspring [41].…”
Section: Discussionsupporting
confidence: 54%
“…Studies investigating the ovaries of female offspring (F1 generation) of smoking mothers showed significantly increased OS levels in oocytes, further leading to apoptosis and the abnormal proliferation of granulosa cells [ 105 ]. This effect continued into the F2 generation with impact on ovarian function not declining until the F3 generation [ 106 ].…”
Section: Factors Related To Os That Lead To Ovarian Agingmentioning
confidence: 99%
“…[17][18][19][20] In females, prenatal exposure to air pollution has been shown to induce a dramatic decrease in the size of the gonads due to alterations in germ cell development, gametogenesis and folliculogenesis that negatively affects the ovarian follicular reserve in offspring. [21][22][23][24][25][26][27] All these studies were done in rodents, mainly by exposure of the entire animals during gestation, and in some cases during lactation as well. 19,24,25 Questions remain which are difficult to answer: was the mother contaminated by ingestion (leaking) of pollutants or by inhalation?…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] All these studies were done in rodents, mainly by exposure of the entire animals during gestation, and in some cases during lactation as well. 19,24,25 Questions remain which are difficult to answer: was the mother contaminated by ingestion (leaking) of pollutants or by inhalation? By which mechanism (acting on germ cell mitosis, or meiosis; or acting on somatic cells differentiation) does pollution affect the gonad?…”
Section: Introductionmentioning
confidence: 99%